2022
DOI: 10.1530/ec-21-0430
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative changes of FGF23 in patients undergoing surgery for primary hyperparathyroidism

Abstract: Background: Fibroblast growth factor-23 (FGF23) is a key regulator of urine phosphate excretion. The aim of the study was to investigate the perioperative (intraoperative and postoperative) changes of plasma intact and C-terminal FGF23 (iFGF23, cFGF23) concentrations in patients with primary hyperparathyroidism (pHPT) submitted to surgery. Materials and methods: Study involved 38 adult patients with pHPT caused by adenoma. PTH levels were investigated intraoperatively (just before the incision and 10 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…However, similarly to Fořtová M et al. ( 22 ), we did not find any significant difference in bone markers levels or correlation between bone markers and FGF23 levels in the 3 study groups.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, similarly to Fořtová M et al. ( 22 ), we did not find any significant difference in bone markers levels or correlation between bone markers and FGF23 levels in the 3 study groups.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have failed to demonstrate significantly higher FGF23 levels in PHPT patients with normal renal function than in healthy controls as well as any change in FGF23 concentration after parathyroidectomy ( 12 , 16 18 ). In contrast, other studies showed that increased FGF23 levels observed in PHPT significantly decreased after successful parathyroidectomy ( 19 22 ). Furthermore, to our knowledge, FGF23 levels have never been previously evaluated in the increasingly recognized NPHPT phenotype.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation